Tuning the morphological structure, light absorption, and photocatalytic activity of Bi2WO6 and Bi2WO6-BiOCl through cerium doping - Hojamberdiev, Mirabbos (2018)
Pharmaceuticals and personal care products are recognized as new classes of water pollutants that receive considerable attention because of their negative environmental impact on aquatic life and humans. Because microbiological and/or conventional secondary physicochemical treatments cannot completely remove those water pollutants, effective advanced oxidation processes using semiconductor-based photocatalysts are needed to ensure their total elimination in water. Here, we report on the tuning of the morphological structure, light absorption, and photocatalytic activity of Bi2WO6 and Bi2WO6-BiOCl through cerium doping. Non-doped and Ce-doped Bi2WO6 and Bi2WO6-BiOCl powders are synthesized by a hydrothermal method, and their adsorption ability and photocatalytic activity are evaluated for the removal of salicylic acid in the dark and under visible light irradiation, respectively. The adsorption affinities and preferential sites of salicylic acid molecules on non-doped and Ce-doped Bi2WO6, BiOCl, and Bi2WO6-BiOCl are computationally predicted using molecular dynamics simulations. When ethylene glycol is replaced by dilute HCl as a solvent in a hydrothermal system, BiOCl is also formed along with Bi2WO6, confirming the successful formation of a Bi2WO6-BiOCl composite. The flower-like hierarchical structures of Bi2WO6 and Bi2WO6-BiOCl can absorb more photon energy due to multiple scattering, charge carriers can easily transfer to the surface/interface, and mesopores can improve the transfer rate of organic molecules, contributing to the overall enhancement in photocatalytic activity. The Bi2WO6-BiOCl samples show higher photocatalytic activity than that of the Bi2WO6 samples for the degradation of salicylic acid due to the formed p–n heterojunction. The optimum concentration of Ce doping is found to be 1 mol% in the Bi2WO6 and Bi2WO6-BiOCl, promoting the effective separation and transfer of photogenerated charge carriers, resulting in high photocatalytic performance, and the sample exhibited good stability.